Postcoital effect on D-Norgestrel pH intrauterine - Kesseru, Esteban (2015)
This study is part of a research program aimed at clarifying the mechanism of contraceptive action of d-Norgestrel on postcoital administration. We have studied the intrauterine fluid pH of a control group consisting of normal women without treatment. The results were compared with a group of patients who had ingested a tablet during Norgestrl d-ovulatory phase of the cycle.